Mentoría relacional con juventud en dificultad social (Investigaciones) - Jaime Ariztegui, Eider (2024)
This article aims to provide evidence on the differential elements of relational mentoring with youth with difficulties in the transition to adulthood, as well as to determine the principles that underlie the permanence of this type of relationship. For this purpose, a combination of quantitative techniques such as the SOATIF and YSoR scales, and qualitative techniques through a semi-structured interview are used to draw complementary conclusions with young people in transition to adulthood participating in relational mentoring programs in Navarre and Vizcaya. In this way, the differential value of mentoring is determined in that it promotes attachment, emotional connection and security with their referent, and, on the other hand, it is observed that positive experiences, understanding, comfort, closeness and listening spaces are predictors of the favorable evolution of relationships. In conclusion, relational mentoring is an effective accompaniment model for building meaningful relationships and secure bonds for youth in difficulty. Moreover, the strengthening of relationships and their permanence is mainly due to the alliance built, the trust with their mentor, the positive experiences and the social exchange perceived in the relationships so relational mentoring offers a significant social support.